Systemic effects of starved fibroblasts culture supernatant on immunosuppressed rats treated with cancer stem cells - Roghayeh Pourbagher; Farideh Feizi; Haleh Akhavan niaki; Davood Sabour; Ebrahim Zabihi; Sahar Gooran; Zeinab Abedian; Fatemeh Majidi; Amrollah Mostafazadeh (Babol University of Medical Sciences, 2020)
Background: The present study aimed to investigate and compare the effect of starved fibroblast culture supernatant (SFS), DMEM and normal saline alone or along with LA7 on dexamethasone-treated immunosuppressed Wistar rats. Methods: After the isolation of fibroblasts from the fresh foreskin of children, it was cultured in serum-free DMEM, and the supernatant collected after 16 hours (16h-SFS). This solution and the other treatments were injected subcutaneously into the rats from each group once daily for 14 days. The liver, intestine and lung histology along with blood cellular and biochemical characteristics were studied. Results: The results showed that dexamethasone as immunosuppressant reduced the body weight. The histological change in the liver was mild fibrosis induced by LA7+16h-SFS. Also, among the different blood cellular and biochemical indices measured,  the eosinophil percentage in the 16h-SFS treated rats ,  glucose levels in the 16h-SFS+LA7 group and triglyceride concentrations  in the 16h-SFS group were changed (p<0.05). Conclusion: This study showed that the secretions of starved fibroblasts especially that combined with LA7 cancer stem cells could induce some minor histological and biochemical changes in immunosuppressed rats, and also it opened a new window for subsequent investigations on unknown mechanisms related to this work.